2012
DOI: 10.3390/ani2010055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fatty Acids on Lipid Traits in the Muscle and Perirenal Fat of Growing Rabbits Fed Mixed Diets

Abstract: Simple SummaryPolyunsaturated fatty acids in human foods have been shown to have health benefits. We investigated the potential to incorporate them into rabbit meat by adding them to the diet. Good relationships between dietary fatty acids (FAs) and their content in longissimus dorsi muscle and perirenal fat of rabbits was established, especially the latter. The results should make it possible to enhance the polyunsaturated fatty acid content of rabbit meat, with benefits to the health of human consumers.Abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…In agreement with our results, previous studies have shown the influence of dietary FA profile on FA deposition in rabbit carcass (Xiccato, 1999;Benatmane et al, 2011;Tres et al, 2014). In addition, good relationships between dietary FA and their content in LM and perirenal fat have been reported by Peiretti (2012) in a review of studies involving 27 diets varying in FA profile. However, individual FA differed in their incorporation in muscle and fat, and regression equations of individual FA in LM and perirenal fat on the same FA in the diet were different for the 2 tissues (Peiretti, 2012).…”
Section: Productive Performance and Carcass Characteristicssupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our results, previous studies have shown the influence of dietary FA profile on FA deposition in rabbit carcass (Xiccato, 1999;Benatmane et al, 2011;Tres et al, 2014). In addition, good relationships between dietary FA and their content in LM and perirenal fat have been reported by Peiretti (2012) in a review of studies involving 27 diets varying in FA profile. However, individual FA differed in their incorporation in muscle and fat, and regression equations of individual FA in LM and perirenal fat on the same FA in the diet were different for the 2 tissues (Peiretti, 2012).…”
Section: Productive Performance and Carcass Characteristicssupporting
confidence: 93%
“…In addition, good relationships between dietary FA and their content in LM and perirenal fat have been reported by Peiretti (2012) in a review of studies involving 27 diets varying in FA profile. However, individual FA differed in their incorporation in muscle and fat, and regression equations of individual FA in LM and perirenal fat on the same FA in the diet were different for the 2 tissues (Peiretti, 2012). A different response to dietary FA in LM and perirenal fat was also observed in our study, as long-chain n-3 PUFA concentrations and n-6/n-3 ratio in PUFA rabbits were greater and lower, respectively, in LM than in perirenal fat.…”
Section: Productive Performance and Carcass Characteristicsmentioning
confidence: 94%
See 1 more Smart Citation
“…Trebušak et al (2011) found that linoleic acid and α-linolenic acid were increased while; palmatic acid was decreased when rabbits fed diet contained linseed oil and consecutively caused a significant decrease in the n-6/n-3 PUFA ratio. Similarly, Peiretti (2012) reported that feeding rabbits with linseed oil increased unsaturated fatty acids, while saturated fatty acids were decreased.…”
Section: Resultsmentioning
confidence: 90%
“…This frequently leads to suboptimal concentration of n-3 PUFA in cell membranes, which may negatively affect physiological regulation, including reproductive response and newborn survival (for review, see Wathes et al, 2007). The proportions of different PUFA in animal tissues reflect the dietary consumption, and particularly in rabbits, there is the capability of modifying the FA profile through the use of unsaturated dietary fat sources (Hernández et al, 2000;Tres et al, 2008Tres et al, , 2009Benatmane et al, 2011;Al-Nouri et al, 2012;Dal Bosco et al, 2012;Peiretti, 2012).…”
Section: Introductionmentioning
confidence: 99%